Priority Level of Emotional Experience in Halal Tourism: Based on Age Generation of Tourists - Octaviany, Vany; Satrya, I Dewa Gde (Universitas Medan Area, 2024)
Great Bandung is a popular tourism destination, offering a variety of attractions that follow Islamic prin-ciples. These attractions cater to diverse emotional experiences, which vary significantly among tourists of different age groups. Research on emotional experiences of tourists based on age in the context of halal tourism is still rare. Therefore, this study aimed to determine “priority level